A produção e o emprego industrial no Brasil e o impacto da abertura comercial (1990-2008) - Monteiro, Luis Emmanuel Rodrigues (2010)
We analyzed the trade liberalization, the level of employment and industrial production between 1990 and 2008. In 1980, the Substitution of Imports Model (MSI) has suffered from the delayed effects of three major adverse shocks that have strangled the balance of payments causing stagflation, it was clear the MSI had been exhausted. The model adopted in 1990, the Washington Consensus Model preaches the trade and financial liberalization as a basis for an economy of solid macroeconomic fundamentals, and its principles were put into practice in Brazil by PICE. Regarding industry, the period between 1990 and 2008 was a period of extraordinary gains in productivity. The relationship between industrial production and unemployment total was positive between 1990 and 2008 as predicted by Okun's Law adapted to the study of the industry. The SS theorem showed that in order to encourage the agricultural sector should be to facilitate the import of machinery and to encourage the industrial sector must become the manpower more productive and cheaper. The Blanchard model demonstrated how the trade unions react to structural changes in the economy. During the economic liberalization and under a framework of external shocks, the strength of unions has declined over the 1980s. Because the process of economic liberalization has brought an increase in the natural unemployment, unions have lost the strength to defend workers' interests effectively. The Lula government made an improvement in the indicators of employment and industrial production. There is no denying that the economy stable has been the best legacy that the previous government left for the Lula administration. However, it is known today that the cost of stabilization policy and trade liberalization in the 1990s could have been shorter if the fear of repeating the failures observed in the very historical and other countries, when under pressure of crisis international economic, had not led to extreme measures to curb demand.